Enhancing Pest and Disease Management Skills for Farmers and Extension Agents in Ethiopia, Lebanon, Morocco, and Tunisia - Kemal, Seid Ahmed; Kumari, Safaa; Boulamtat, Rachid; Moukahel, Abdulrahman; Kassaw, Admasie; Choueiri, Elia; Bencheqroun, Sanae Krimi; Elwazziki, Hanane; Boughlala, Mohamed; Kharrat, Mohamed; Najar, Asma; Abbes, Zouhaier (International Center for Agricultural Research in the Dry Areas, 2024)
During the 2023/2024 cropping season, training and field days was given to farmers, development agents and Office of agriculture experts in four countries (Ethiopia, Lebanon, Morocco, and Tunisia) to improve their knowledge and skill gaps on managing new and emerging pests and diseases before and after planting crops. A total of 159 farmers (22% female) and experts were trained in the four countries. In addition, six field days were organized in the above four countries and around 200 farmers and development agents participated in the events. In Lebanon, training was given on management of fall armyworm on summer planted maize at Qob Elias of the PHI-IP site. In Ethiopia, Tunisia and Morocco, the training and field days focused on management of viruses, aphids, and parasitic weeds on faba bean.